Pengaruh Etika Kerja dan Lingkungan Kerja Terhadap Kualitas Kerja Pegawai Pada Direktorat Kementrian Kelautan Distrik Navigasi Kelas 1 Palembang - Putra, Muhammad Meisandy Pratama; Robyardi, Erfan; Heryati, Heryati (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to test the hypothesis of the influence of work ethics and work environment on work quality. The research method used is associative quantitative. The population of this study were all employees, totaling 126 people at the Directorate of the Ministry of Maritime Affairs, Class 1 Navigation District, Palembang. Sampling technique using saturated samples. Sources and data collection techniques for this research are primary data by distributing questionnaires to respondents and secondary data by collecting documentation and literature relevant to the research. The data analysis technique used is a multiple linear test, correlation coefficient test and determination coefficient test (R2). The hypothesis test used is the t test and F test. The results of the t test were obtained at a significant value of the work ethic variable of 0.00, and the work environment variable was 0.00, so it was partially concluded that it could have an effect. While the results of the F test are sig. on the variable quality of work of 0.00, the work ethic and work environment influence simultaneously or simultaneously on the quality of employee work